2004
DOI: 10.1191/0267659104pf733oa
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone prevents inflammatory reaction occurring during cardiopulmonary bypass: effects on TNF-α, IL-6, IL-8, IL-10

Abstract: Objective: This study examined the correlation between tumour necrosis factor-alfa (TNF-α), interleukin (IL)-6 and IL-8, IL-10 and methylprednisolone pretreatment. Methods: This is a prospective, randomized and double-blinded study. Sixty patients undergoing coronary artery bypass grafting (CABG) were randomized to receive either intravenous methylprednisolone (n=30, Group M) or intravenous placebo (n=30, Group S). The patients received intravenously either 30 mg/kg methylprednisolone (Group M) or placebo (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
2
28
2
Order By: Relevance
“…Corticosteroid resistance could result in reduced inhibition of IL8 by methylprednisolone and thus affect its downstream interactions [34]. IL8 expression was not significantly different between responders and non-responders in this study despite a previous report of elevated IL8 mRNA levels in active UC [41].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Corticosteroid resistance could result in reduced inhibition of IL8 by methylprednisolone and thus affect its downstream interactions [34]. IL8 expression was not significantly different between responders and non-responders in this study despite a previous report of elevated IL8 mRNA levels in active UC [41].…”
Section: Discussioncontrasting
confidence: 63%
“…A diagrammatic representation of the immediate interactome of methylprednisolone indicated an inhibitory action on K60 , also known as IL8 (Figure 1) [34]. In turn, IL8 is a known inducer of CEACAM1 and MMP8 [35], [36], [37], and it also interacts with BPI , LCN2 and PPBP [36], [38], [39], [40].…”
Section: Resultsmentioning
confidence: 99%
“…Corticosteroids have been used in patients undergoing cardiac surgery with CPB to reduce the systemic infl ammatory response syndrome induced by CPB, despite the fact that few well-controlled studies exist to support their use. 15 Their use is based on limited studies suggesting that corticosteroids may mitigate the infl ammatory response associated with CPB through the reduction of complement activation and the release of infl ammatory cytokines, 5,6,8 and an increase in IL-10 8 and antiinfl ammatory cytokines. signifi cance ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic intervention was based on the observation that perioperative corticosteroids can reduce complement activation and the release of infl ammatory cytokines associated with cardiopulmonary bypass (CPB). [4][5][6][7][8] However, the clinical benefi t of this intervention is uncertain. Studies assessing the use of corticosteroids in patients who undergo CPB are limited by a small number of patients or an absence of physiologic or clinical correlates.…”
mentioning
confidence: 99%
“…[19] It does appear from this study that ketamine, like glucocorticoids, though successful in reducing serum level of inflammatory markers in the post-CPB period, does not produce improvement in readily measured clinical markers of pulmonary function. Though corticosteroids have been shown to reduce the serum inflammatory markers, [20,21] neither systemic nor inhaled corticosteroids have been shown to offer clinical benefits measured in terms of pulmonary dysfunction, oxygenation, duration of mechanical ventilation, hemodynamic benefit, or improvement in pain control in patients undergoing CPB. [5,22,23] In addition, Cho et al, have studied 50 patients undergoing off-pump CABG and concluded that administration of 0.5 mg/kg of ketamine at induction of general anesthesia did not result in significant changes in serum levels of CRP, IL 6, TNF alpha and cardiac enzymes [24] even though off-pump CABG has been shown to induce marked and similar inflammatory response as that of CPB.…”
Section: Resultsmentioning
confidence: 99%